Hans-Georg Gadamer i hermeneutyczny problem aktualizacji tekstów biblijnych - Adamczewski, Bartosz (The Biblical Annals, 2017)
One of the weakest points of the historical-critical method of interpreting the Bible is the lack of means of appropriate application of the message of biblical texts (treated as texts from a distant past) to our present reality. The theory of German philosopher Hans-Georg Gadamer may provide modern readers of the Bible with various intersubjectively verifiable ways of actualization of biblical texts: dramaturgical, liturgical, iconical, based on tradition and authority, juridical, and imparting wisdom. The last one seems to be the most appropriate for seeking and communicating the message of the Bible in the context of modern European, agnostic culture.